The Bacteria Contamination of Red Local and Imported Meat - Abid Ali, Samir; jawd, Abdul Amir; mahdi, salah (Iraqi Journal of Science, 2024)
This study has been achieved to detect the bacterial contamination of red localand imported meat (Saudi, Australian and Indian). 12 Kg of meat were bought fromsix different places of Baghdad (Aldura, Almahmodia, ,Algehad, Alsader city,Alkhademia, Albyiaa). Meat extraction samples were cultured in different diagnosticand nutrient cultures to detect bacterial contamination which represented mainly ofColiform, Staphylococcus aureus and Salmonella bacteria. The results of theimported meat showed high level in the count of those bacteria in addition to another group (not diagnosed) mentioned as “different species “of bacteria. All of them reached the maximum level of permitted range which specified by “Central Organization for Standardization and Quality Control”, while the average bacterial count in the local meat was less than of the normal range of limits. Salmonella bacteria showed negative results in all samples.